Full range leadership style and its effect on effectiveness, employee satisfaction, and extra effort: an empirical study - Garzón-Lasso, Fernando; Serrano-Malebrán, Jorge; Arenas-Arango, Sandra; Molina, Carlos (Frontiers in Psychology, 2024)
The purpose of this study is to determine if there is a positive relationship between full-range leadership and employees' effort, efficiency, and satisfaction. A questionnaire was administered to 577 executives from Colombian companies, and the data was analyzed using a partial least squares structural equation modeling (PLS-SEM) approach. The results show that both transformational and transactional leadership have a direct and significant impact on extra effort, effectiveness, and satisfaction, with transformational leadership having the greatest impact on these factors. Conversely, passive-avoidant leadership has negative effects on these three constructs. This study validates the effectiveness of the MLQ 5X in a South American country, a geographical region where such studies are in their early stages. Finally, the whole range of leadership styles—transformational, transactional, and passive-avoidant—is looked at. These styles are seen as second-order constructs that challenge latent multidimensional models as they emerge.